Public policy resources - Knoepfel, Peter (Policy Press, 2018)
Building on Knoepfel's previous book, Public policy analysis, this book offers a conceptually coherent view of ten public policy resources: force, law, personal, money, property rights, information, organisation, consensus, time and political support. The book demonstrates the interplay of the different resources in a conceptually coherent framework and presents numerous illustrations of ways of mobilising the resources and managing them in a sustainable way, resource exchanges and the role of institutions governing the interrelationships between actors and resources. The book will be valuable to postgraduate students as well as those working in policy programming and implementation across both public and private sectors and in non-governmental organisations.